Odpowiedzi

Najlepsza Odpowiedź!
2010-01-01T23:17:56+01:00
5x(x+y+z)=4
2y(x+y+z)=6
4z(x+y+z)=4

5x² + 5xy + 5xz = 4
2xy + 2y² + 2yz = 6
4xz + 4yz + 4z² = 4

5x² + 5xz - 4 = 5xy |:5x
x + z - (4/5x) = y
y=⅕x + z

2x(⅕x + z) + 2(⅕x + z)² + 2z(⅕x + z) = 6 |:2
4xz + 4z(⅕x + z) + 4z² = 4 |:4

x(⅕x + z) + (⅕x + z)² + z(⅕x + z) = 3
xz + z(⅕x + z) + z² = 1

⅕x² + xz + (⅕x + z)² + ⅕xz + z² = 3
xz + ⅕xz + z² + z² = 1 |*5

5xz + xz + 10z² = 5
x(5z + z) = 5 - 10z²
x * 6z = 5-10z²
x= (5-10z²)/6z

teraz do tego równania:
⅕x² + xz + (⅕x + z)² + ⅕xz + z² = 3

musisz podstawić x, potem wyliczyć każde z niewiadomych.